Media Framing of Larry Nassar and the USA Gymnastics Child Sex Abuse Scandal. - Smith, Lauren Reichart; Pegoraro, Ann (Journal of Child Sexual Abuse)
The framing of child sex abuse in media has previously been examined to uncover the potential ways news media could influence public perception about the issue. This mixed methods analysis of the Larry Nassar sex abuse scandal involving USA gymnastics and Michigan State University, grounded in the principles of framing theory, examines the patterns in coverage, as well as the episodic and thematic frames evident in the coverage of the scandal and its victims. Findings fall in line with past research on child sex abuse; framing is done primarily at the episodic level, focusing on the individual responsible, detailed accounts of the abuse of the victims, and isolating the instances of abuse to the specific organizations, while ignoring the broader themes of prevention and societal impacts. Implications for framing, attitudes toward girls and women in sport, and implications for abuse in sport are discussed.